Lactic Acid Fermentation to Re-cycle Apple By-Products for Wheat Bread Fortification - Cantatore, Vincenzo; Filannino, Pasquale; Gambacorta, Giuseppe; De Pasquale, Ilaria; Pan, Stefan; Gobbetti, Marco; Di Cagno, Raffaella (Frontiers in Microbiology, 2019)
Apple by-products (ABP) underwent fermentation (48 h at 30°C, Fermented-ABP) with a selected binary culture of Weissella cibaria PEP23F and Saccharomyces cerevisiae AN6Y19. Compared to Raw-ABP and Chemically Acidified-ABP (CA-ABP), fermentation markedly increased the hydration properties of ABP. Fermentation led to the highest increases of total and insoluble dietary fibers (DF). Raw-, CA- and Fermented-ABP, at 5 and 10% (w w-1 of flour), were the ingredients for making fortified wheat breads. Addition of ABP and mainly fermentation enhanced dough water absorption and stability, and markedly increased the content of DF. Fortification mainly with 5% of Fermented-ABP did not interfere with bread rheology and color. As shown by profiling volatile compounds, Fermented-ABP imparted agreeable and specific sensory attributes, also appreciated by sensory analysis, and decreased bread hydrolysis index, and delayed mold contamination and firming. Fermented-ABP were suitable ingredients to fortify wheat bread formula, which agreed with bio-economy and environmental sustainability concepts.